Analisis Kinerja Keuangan Pada PT Hutama Karya Jakarta - Anggita Herlina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Analysis of financial performance is the most important thing for business people because financial performance is an indicator to find out whether the business being run will continue to run well in the future or not. All companies will analyze the company's financial performance so that the company can get an overview of the company's financial condition. One of them is a State-Owned Enterprise (BUMN) in Indonesia, namely PT Hutama Karya which is engaged in construction, as well as property and infrastructure development. The purpose of this study was to determine the condition of PT Hutama Karya's financial performance as measured using a liquidity ratio based on data, information, and records from the financial statements of PT Hutama Karya in 2020 to 2022. The results of the study show that PT Hutama Karya's financial performance in 2020 to 2022 can be said to be quite good because the company is able to pay its short-term debt. This is because the company's current assets are managed properly by the company's financial management which makes it increase significantly and there is a decrease in its current debt.